The wide variation of definitions of genetic testing in international recommendations, guidelines and reports - Sequeiros, Jorge (Springer-Verlag, 2012)
In spite of being very commonly used, the term genetic testing is debatable and used with several meanings. The diversity of existing definitions is confusing for scientists, clinicians and other professionals, health authorities, legislators and regulating agencies and the civil society in general, particularly when genetic testing is the object of guidelines or legal documents. This work compares definitions of genetic testing found in recommendations, guidelines and reports from international institutions, policy makers and professional organizations, but also in documents from other stakeholders in the field, as the pharmaceutical industry, insurers, ethics bodies, patient organizations or human-rights associations. A systematic review of these documents confirmed the extreme variability existing in the concepts and the ambiguous or equivocal use of the term. Some definitions (narrower) focus on methodologies or the material analysed, while others (broader) are information- or context-based. Its scope may range from being synonymous of just DNA analysis, to any test that yields genetic data. Genetic testing and genetic information, which may be derived from a range of medical exams or even family history, are often used interchangeably. Genetic testing and genetic screening are sometimes confused. Human molecular genetics (a discipline) is not always distinguished from molecular biology (a tool). Professional background, geographical context and purpose of the organizations may influence scope and usage. A common consensus definition does not exist. Nevertheless, a clear set of precise definitions may help creating a common language among geneticists and other health professionals. Moreover, a clear context-dependent, operative definition should always be given. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-012-0084-2) contains supplementary material, which is available to authorized users.